If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + -48 = q + 36 Reorder the terms: -48 + 4q = q + 36 Reorder the terms: -48 + 4q = 36 + q Solving -48 + 4q = 36 + q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1q' to each side of the equation. -48 + 4q + -1q = 36 + q + -1q Combine like terms: 4q + -1q = 3q -48 + 3q = 36 + q + -1q Combine like terms: q + -1q = 0 -48 + 3q = 36 + 0 -48 + 3q = 36 Add '48' to each side of the equation. -48 + 48 + 3q = 36 + 48 Combine like terms: -48 + 48 = 0 0 + 3q = 36 + 48 3q = 36 + 48 Combine like terms: 36 + 48 = 84 3q = 84 Divide each side by '3'. q = 28 Simplifying q = 28
| 2[4(2x-1)-(5x-3)]=7x+2 | | 18+8j=10 | | e-5.6=68 | | 52=3x | | -5(2+2q)=2(5+5q) | | 2(4)+4+4+2=2(4)+10 | | -195=x+5(9-5x) | | 2a-41=a+21 | | P=90-2(19) | | F(x)=6(x+8)-3 | | 7r=3r | | 11+2b=15 | | 3s-75=s+15 | | 3=11-2x-3x+5 | | P(19)=90-2(19) | | z+87=2z | | 16+2q=12 | | N=-2+x | | -5=12(6x-2)+7x | | s^2+(4s+3)=y | | P(19)=90-2x | | 15-2/5f=-6 | | 19.2j+3(17.3j+4.57)=3(9.8j-2.38) | | X=-2+n | | 14-(X+8)=8X-3 | | 408=-8(10n+9) | | (5-4i)(2+6i)=0 | | 10=z^2+3z | | 0.33(2x-1)=0.5(3x+1) | | g-62=15 | | 16+24=-5(3x-8) | | 6(2x+1)=2x-6x |